Auditory attention in individuals with tinnitus - Lima,Daviany Oliveira (2020)
Abstract Introduction Tinnitus is characterized by the presence of a sound in the absence of external sound stimulus. In individuals with normal audiometry, it may be associated with auditory attention difficulty, especially in those who report high tinnitus annoyance. Objective To investigate auditory attention ability in individuals with tinnitus complaint. Methods Cross-sectional analytical observational study. We evaluated 30 volunteers with normal hearing (up to 25 dBHL): 15 with tinnitus (test group) and 15 with no complaints (control group), aged between 18-40 years. The volunteers answered the tinnitus handicap inventory questionnaire and a visual analogue scale. Subsequently, a basic audiological evaluation (meatoscopy, tonal and vocal audiometry, and imittanciometry) and psychoacoustic measures of tinnitus (loudness and pitch) were performed. To evaluate auditory attention, the following tests were performed: auditory cognitive evoked potential (P300), central auditory processing tests (dichotic digits test and speech-in-noise test) and sustained auditory attention ability test. Results In the tinnitus handicap inventory, individuals with tinnitus had a mean score of 37.78 (±27.05), characterized as moderate degree. In the dichotic digits test (binaural separation), a difference was observed between the groups in both ears. Moreover, there was a difference in the speech-in-noise test in both ears (RE: p = 0.044; LE: p = 0.019), in P300 (p = 0.049) and in total sustained auditory attention ability test (p = 0.032). Also, there is a negative correlation between sustained auditory attention ability test, decrease in attentiveness and binaural integration (RE: p = 0.044; LE: p = 0.048). Conclusions Individuals with tinnitus had a poorer performance compared to the control group regarding auditory attention ability. Therefore, it is inferred that tinnitus is associated with poor performance in selective and sustained auditory attention in the assessed volunteers. These aspects should be considered for the management of patients with tinnitus.